2018
DOI: 10.3390/molecules23071782
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of LLDPE and Surface-Modified Cellulose Nanocrystals Prepared by Melt Processing

Abstract: Cellulose nanocrystals (CNCs) were surface modified by esterification in tetrahydrofuran (THF) at 25 °C using different catalysts and anhydrides bearing different alkyl side chain lengths. Unmodified and acetic anhydride (AcAnh)-modified CNCs were studied as potential nanofillers for linear low-density poly(ethylene) (LLDPE). Nanocomposites were prepared by melt processing. Determination of the size and size distribution of CNCs in the nanocomposites by SEM revealed an enhanced compatibility of the AcAnh-modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“… 190 Different kind of polymers have been used as the matrixes. For example, A. Anžlovar et al (2018) 184 demonstrated that acetic anhydride-modified CNCs can act as reinforcement in linear low-density polyethylene (LLDPE) composites. The authors found an improvement in the compatibility between CNCs and the matrix, resulting in a 90% increase in the breaking strain of the composite.…”
Section: Effect Of the Most Used Nanoparticles In Food Packagingmentioning
confidence: 99%
“… 190 Different kind of polymers have been used as the matrixes. For example, A. Anžlovar et al (2018) 184 demonstrated that acetic anhydride-modified CNCs can act as reinforcement in linear low-density polyethylene (LLDPE) composites. The authors found an improvement in the compatibility between CNCs and the matrix, resulting in a 90% increase in the breaking strain of the composite.…”
Section: Effect Of the Most Used Nanoparticles In Food Packagingmentioning
confidence: 99%
“…Comparison microscopic image of; (B) bacterial nanocellulose (Li et al, 2017): Published by The Royal Society of Chemistry, (C) nanofibrillated cellulose: Reprinted (adapted) with permission from Saito et al (2007). Copyright (2007) American Chemical Society and, (D) nanocrystalline cellulose (Anžlovar et al, 2018). of temperature, agitation, and time (Clemons, 2016;Charreau et al, 2020).…”
Section: Plant Nanocellulosesmentioning
confidence: 99%
“…Various polymers have been employed as the matrixes. Anzlovar et al (Anzlovar et al 2018) reported that the acetic anhydridemodified CNCs could serve as a reinforcing agent for linear low-density poly(ethylene)…”
Section: Food Packagingmentioning
confidence: 99%